1979
DOI: 10.1007/bf00506554
|View full text |Cite
|
Sign up to set email alerts
|

A structure-activity study on the influence of phenolic compounds and bioflavonoids on rat renal prostaglandin synthetase

Abstract: The stimulating or inhibiting influences of 33 phenolic compounds on the prostaglandin synthetase of rat renal medulla were tested. Dihydroxyphenylcarbonic acids clearly proved to be activators of the prostaglandin synthetase. Dimethoxyphenylcarbonic acids were ineffective. Aminoethylphenols as well as p-substituted monohydroxybenzenes with a carbonic acid side chain were clear stimulators in contrast to their alkyl derivatives which are pronounced inhibitors. Among the tested bioflavonoids (+)-cyanidanol-3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Phloretin also inhibits several membrane transport mechanisms [30]. Flavonoids have been shown to inhibit prostaglandin synthetase [31,32]. Nevertheless, possible inhibition of platelet cyclo-oxygenase by flavonoids cannot be implied as the mechanism of inhibition of aggregation by ADP or thrombin, because it has been demonstrated that washed human platelets aggregate in the presence of ADP or thrombin independently of the formation of prostaglandin endoperoxide and thromboxane A 2 [33].…”
Section: Discussionmentioning
confidence: 99%
“…Phloretin also inhibits several membrane transport mechanisms [30]. Flavonoids have been shown to inhibit prostaglandin synthetase [31,32]. Nevertheless, possible inhibition of platelet cyclo-oxygenase by flavonoids cannot be implied as the mechanism of inhibition of aggregation by ADP or thrombin, because it has been demonstrated that washed human platelets aggregate in the presence of ADP or thrombin independently of the formation of prostaglandin endoperoxide and thromboxane A 2 [33].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5 shows (14). However, the possibility that norepinephrine induces PG synthesis in dog renomedullary slices simply by its participation as a phenolic cofactor in the cyclooxygenation can be disregarded because much a higher concen tration (0.5-1 mM) of phenolic compounds seems to be required for this reaction (24,25) than for the stimulation of PG synthesis in our system (5 ,uM).…”
Section: Resultsmentioning
confidence: 94%
“…The hydrogen-donating ability of antioxidants is responsible for the reduction of DPPH radical to DPPHH [32,33]. In hydrazides and their metal complexes, a-or bhydrazinic nitrogen could be the site for removal of hydrogen radical required for the reduction of DPPH.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%